Avaliação de desempenho do servidor público, na esfera da educação superior da UFSM, enquanto instrumento de gestão de pessoas - Chansis, Loiva Isabel Marques (2013)
From the viewpoint of the organization and especially the Public organization, the thematic of the process of Functional Performance Assessment, arises as a timely issue for the efficiency, quality in the services by the servants, gaining more space as it affects the capability of the own survival of the organization. Currently in the public, it is strongly occurring attempts to implement an assessment of performance to provide information about the civil servants which are used to subsidize a process of personal management. They are instruments that are growing to value the civil servants, and to improve working processes. A great challenge due to the organizational culture of the public sector, because according to Marconi (2004) the effective performance assessment will be possible through the development and culture focused on results, with an alignment of the goals of the individual and of the team to the goals of the organization. From this viewpoint, this dissertation project has as RESEARCH THEME The performance assessment of the public servant , in the sphere of Higher Education at UFSM Good Practices, while instrument for people management, systematizing all the work accomplished so far, regarding the performance assessment of the administrative technician in Education. According to the law N 11.091, de 12/01/2005, which deals with the structure of the Career Plan of Technical and Administrative Positions in Education, under the Federal Institutions linked to the Ministry of Education, it was brought into light the use of a functional assessment system in universities. At UFSM, the Dean of Human Resources is the organ responsible for implementing the program of performance assessment, according to what provides the Career Plan of the Technical and administrative positions in education- PCCTAE (Law 11091/05) having the challenge of instilling in the institution the performance assessment as an important tool for people management. In order to achieve this goal, there will be a research of quantitative, bibliographical and documental nature. Concerning the research strategy, there will be used the case study whose organization, object of study will be the Federal University of Santa Maria. The data collection will be through the analysis of documentation, legislation and reports provided by the Dean of Human Resources. The conclusion of my dissertation is the Pedagogical Primer, which contains all the publicizing and systematization of the process of implementation of the Program of Performance Assessment at UFSM, in order to help as studies and parameters for the Federal Institutions of Education.